Những câu hỏi liên quan
Charlet
Xem chi tiết
Trần Huỳnh Thanh Long
Xem chi tiết
gfriend
Xem chi tiết
nguyenthithuytien
Xem chi tiết
phạm minh tâm
11 tháng 9 2017 lúc 20:47

xét \(\sqrt{\frac{1}{a^4}+\frac{1}{b^4}+\frac{1}{\left(a^2+b^2\right)^2}}=\sqrt{\frac{b^4\left(a^2+b^2\right)^2+a^4\left(a^2+b^2\right)^2+a^4b^4}{a^4b^4\left(a^2+b^2\right)^2}}=\sqrt{\frac{a^8+b^8+2a^2b^6+a^4b^4+a^4b^4+2a^6b^2+a^4b^4}{\left[a^2b^2\left(a^2+b^2\right)\right]^2}}\)=\(\sqrt{\frac{\left(a^4+b^4\right)^2+2a^2b^2\left(a^4+b^4\right)+a^4b^4}{\left[a^2b^2\left(a^2+b^2\right)\right]^2}}=\sqrt{\frac{\left(a^4+b^4+a^2b^2\right)^2}{\left[a^2b^2\left(a^2+b^2\right)\right]^2}}\)

Bình luận (0)
Nguyễn Tùng
Xem chi tiết
Mr Lazy
1 tháng 7 2015 lúc 11:36

\(A=\frac{1}{a^4}+\frac{1}{b^4}+\frac{1}{\left(a^2+b^2\right)^2}=\frac{\left(a^4+b^4\right)\left(a^2+b^2\right)^2+a^4b^4}{a^4b^4\left(a^2+b^2\right)^2}\)

\(=\frac{\left(a^4+b^4\right)\left(a^4+b^4+2a^2b^2\right)+a^4b^4}{\left[a^2b^2\left(a^2+b^2\right)\right]^2}=\frac{\left(a^4+b^4\right)^2+2a^2b^2\left(a^4+b^4\right)+\left(a^2b^2\right)^2}{\left[a^2b^2\left(a^2+b^2\right)\right]^2}\)

\(=\frac{\left(a^4+b^4+a^2b^2\right)^2}{\left[a^2b^2\left(a^2+b^2\right)\right]^2}\)

\(\Rightarrow B=\frac{1}{a^2+b^2}+\frac{1}{\left(a+b\right)^2}+\sqrt{A}\)\(=\frac{1}{a^2+b^2}+\frac{1}{\left(a+b\right)^2}+\frac{\left(a^2+b^2\right)^2-a^2b^2}{a^2b^2\left(a^2+b^2\right)}\)

\(=\frac{1}{a^2+b^2}+\frac{1}{\left(a+b\right)^2}+\frac{a^2+b^2}{a^2.b^2}-\frac{1}{a^2+b^2}\)

\(=\)\(\frac{\left(a^2+b^2\right)\left(a+b\right)^2+a^2b^2}{a^2b^2\left(a+b\right)^2}=\frac{\left(a^2+b^2\right)\left(a^2+b^2+2ab\right)+a^2b^2}{\left[ab\left(a+b\right)\right]^2}\)

\(=\frac{\left(a^2+b^2\right)^2+2\left(a^2+b^2\right).ab+\left(ab\right)^2}{\left[ab\left(a+b\right)\right]^2}\)

\(=\frac{\left(a^2+b^2+ab\right)^2}{\left[ab\left(a+b\right)\right]^2}=\left[\frac{a^2+b^2+ab}{ab\left(a+b\right)}\right]^2\)

\(\Rightarrow\sqrt{B}=\left|\frac{a^2+b^2+ab}{ab\left(a+b\right)}\right|=\frac{a^2+b^2+ab}{\left|ab\left(a+b\right)\right|}\)

 

 

Bình luận (0)
Nguyễn Hồng Thắm
Xem chi tiết
Nguyễn Hồng Thắm
6 tháng 10 2018 lúc 11:12

Ai giải giúp mình bài 1 với bài 4 trước đi

Bình luận (0)
Charlet
Xem chi tiết
Nguyễn Quốc Gia Huy
11 tháng 8 2017 lúc 10:22

Bài 1: 

Ta có:

\(\left(a-b+c\right)^3=a^3-b^3+c^3-3a^2b+3a^2c+3ab^2+3b^2c+3ac^2-3bc^2-6abc\)

\(\Rightarrow\left(\sqrt[3]{\frac{1}{9}}-\sqrt[3]{\frac{2}{9}}+\sqrt[3]{\frac{4}{9}}\right)^3=\frac{1}{9}-\frac{2}{9}+\frac{4}{9}-\frac{1}{3}.\sqrt[3]{2}+\frac{1}{3}.\sqrt[3]{4}+\frac{1}{3}.\sqrt[3]{4}+\frac{2}{3}.\sqrt[3]{2}\)

\(+\frac{2}{3}.\sqrt[3]{2}-\frac{2}{3}.\sqrt[3]{4}-\frac{4}{3}=\sqrt[3]{2}-1\)

\(\Rightarrow\sqrt[3]{\sqrt[3]{2}-1}=\sqrt[3]{\frac{1}{9}}-\sqrt[3]{\frac{2}{9}}+\sqrt[3]{\frac{4}{9}}\)

Bình luận (0)
Đỗ Thị Diễm Khanh
Xem chi tiết
Nguyễn Kim Khánh Hà
10 tháng 5 2016 lúc 16:49

\(D=\left(\frac{a-b}{a^{\frac{3}{4}}+a^{\frac{1}{2}}.b^{\frac{1}{4}}}-\frac{a^{\frac{1}{2}}-b^{\frac{1}{2}}}{a^{\frac{1}{4}}+b^{\frac{1}{4}}}\right):\left(a^{\frac{1}{4}}-b^{\frac{1}{4}}\right)^{-1}\sqrt{\frac{a}{b}}\)

   \(=\left[\frac{a-b}{a^{\frac{1}{2}}\left(a^{\frac{1}{4}}+b^{\frac{1}{4}}\right)}-\frac{a^{\frac{1}{2}}-b^{\frac{1}{2}}}{a^{\frac{1}{4}}+b^{\frac{1}{4}}}\right]:\left(a^{\frac{1}{4}}-b^{\frac{1}{4}}\right)^{-1}\sqrt{\frac{b}{a}}\)

    \(=\frac{a-b-a+a^{\frac{1}{2}}.b^{\frac{1}{2}}}{a^{\frac{1}{2}}\left(a^{\frac{1}{4}}+b^{\frac{1}{4}}\right)}.\frac{1}{\left(a^{\frac{1}{4}}-b^{\frac{1}{4}}\right)}=\frac{b^{\frac{1}{2}}}{a^{\frac{1}{2}}}\frac{\left(a^{\frac{1}{4}}-b^{\frac{1}{4}}\right)}{\left(a^{\frac{1}{4}}-b^{\frac{1}{4}}\right)}\sqrt{\frac{a}{b}}.\sqrt{\frac{a}{b}}=1\)

Bình luận (0)
tranhang
Xem chi tiết
Chu Bá Đạt
11 tháng 4 2017 lúc 17:56

Khó quá ; đề ở đâu vậy bạn ........

Bình luận (0)